ANIMASI INTERAKTIF PENGENALAN HEWAN KHAS PULAU INDONESIA BERBASIS ANDROID PADA TK KUPU-KUPU MUNGIL BEKASI - Septi Eka Hardyana; Herlawati . . (Universitas Bina Sarana Informatika, 2016)
Abstract — Concentration of kindergarten children were veryminimal compared to adults make teachers need to be extra in thedelivery of material in the learning process because kids get boredeasily with the media book. Many types and concepts that must beabsorbed and used the learning process is still classically causesless understanding children and teachers must often repeat thelearning materials. Teaching with lecture method and the lack ofprops make children less interested in learning. The method used toconvey information one through multimedia-based learningandroid with needs analysis, system design, code generation,testing, support. The purpose of this learning system is to helpchildren learn animal diversity typical kindergarten on an island inIndonesia. Fill delivered a simple material. There are also quizexercises to test children's understanding about this matter andalso the game to provide entertainment in the study. In additionandroid multimedia-based learning can also help teachers delivermaterial with the introduction of the animals easier. Studying theanimals unique to the island in Indonesia needs to be ways orstrategies that can facilitate children in learning. To attractattention, is necessary to create classroom situation makes thechildren motivated to learn. One way is to use teaching aids ormedia when teachers teach. Rapid advances in technology,especially information technology encourages people to developmedia that can be used anytime and anywhere.